2022
DOI: 10.3390/app12062819
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Urban Infrastructure Resilience via Pressure-State-Response Framework in Four Chinese Municipalities

Abstract: Urban infrastructure (UI), subject to ever-increasing stresses from artificial activities of human beings and natural disasters due to climate change, assumes a key role in modern cities for maintaining their functional operations. Therefore, understanding UI resilience turns essential. Based on the Pressure-State-Response (PSR) model, this paper built a comprehensive evaluation index system for urban infrastructure resilience evaluation. Four municipalities, including Beijing, Tianjin, Shanghai, and Chongqing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The current index system for urban infrastructure and its resilience is mainly constructed in terms of energy, water supply and drainage, transportation, communication and other municipal utilities. For example, Chen et al described the state of infrastructure resilience in terms of the gas penetration rate, water penetration rate, and road area per capita [6]. Liu, Chen, Tao, Bai, and Zhang et al constructed indicator systems including the daily domestic water consumption per capita, water supply pipeline density, drainage pipeline density, and road area per capita [5, 7-13, 26, 27, 40-42].…”
Section: Construction Of the Urban Infrastructure Resilience Index Sy...mentioning
confidence: 99%
See 3 more Smart Citations
“…The current index system for urban infrastructure and its resilience is mainly constructed in terms of energy, water supply and drainage, transportation, communication and other municipal utilities. For example, Chen et al described the state of infrastructure resilience in terms of the gas penetration rate, water penetration rate, and road area per capita [6]. Liu, Chen, Tao, Bai, and Zhang et al constructed indicator systems including the daily domestic water consumption per capita, water supply pipeline density, drainage pipeline density, and road area per capita [5, 7-13, 26, 27, 40-42].…”
Section: Construction Of the Urban Infrastructure Resilience Index Sy...mentioning
confidence: 99%
“…Previous studies have shown that there are complex spatial and temporal dynamics underlying the resilience of urban infrastructure, as evidenced by the exploration of its spatial and temporal divergence [6,[18][19][20][21][22][23][24][25][26][27][29][30][31][32][33][34][35]. However, was a spatial spillover effect of UIR observed?…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, Ruan established a system of urban resilience indicators with a coupled PSR model and resilience process [27]. Chen evaluated urban infrastructure resilience using the PSR model [28]. Therefore, this paper starts from the connotation of RSR, dismantles the complex process of community resilience, introduces the PSR model, and sorts out the pressure, state, and feedback of communities in the face of risk, which provides support for this paper to build the community resilience evaluation system.…”
Section: Introductionmentioning
confidence: 99%